(untitled) (Western European Journal of Modern Experiments and Scientific Methods, 2025)
This article analyzes the opportunities, advantages, and practical outcomes of applying artificial intelligence technologies in the education sector. The study highlights the role of AI in digital transformation processes in education, personalized learning, automated assessment, improving pedagogical efficiency, and expanding inclusive education opportunities. In addition, technological, pedagogical, social, and ethical challenges are discussed, along with an analysis of international (UNESCO) and national initiatives aimed at addressing these challenges.